PERANCANGAN PEMBELAJARAN VIRTUAL OVOP SEBAGAI SARANA PENGEMBANGAN ILMU EKONOMI DI ERA DISRUPSI - Emma Yunika Puspasari (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
ABSTRACTHegemony classical in economics raises the prisoner’s dilemma related to the ever-changing paradigm of disruption education. Overcoming this dilemma requires a choice of orientation for the Virtual OVOP design, which determines the commitment to resolve the disruption of education polemic. The learning innovation projected was the design of Virtual OVOP learning as a means of developing economics. The affirmation of the concept of economic learning between central and peripheral had been demonstrated by classical economics’, which magnum opus. We should fossilize it in the frame of cultural awareness to exploit the local potential. The idealization of the existence of learning through exploiting the economic potential in the spirit of trying to be together in mainstream education can be realized more clearly with the Virtual OVOP learning design. Learning virtual OVOP using the research and development model approach is a One Village One Product (OVOP) model that was part of learning based on educational videos and animated multimedia on mapping feature products of a rural area and the efficient use of local resources to build a welfare rural.Keywords: Virtual OVOP, Educative Video, Welfare Rural